압력용기용 SA516/70강의 고온파괴인성평가 - 박경동(K. D. PARK); 김정호(J. H. KIM); 윤한기(H. K. Yoon); 박원조(W. J. PARK) (Han-guk haeyang gonghak hoeji (Online), 2001)
Elastic-plastic fracture toughness $J_{lc}$ can be used as an effective design criterion in elastic plastic fracture mechanics. Most of these systems are$J_{lc}$ $J_{lc}$ value at high temperature must be determined for use of integrity evaluation and designing of such systems. Elastic-plastic fracture toughness $J_{lc}$ tests were performed on SA516/70 carbon steel plate and test results were analyzed according to ASTM E 813-87, ASTM E 813-89 and ASTM E 1152-87.safety and integrity are required for reactor pressure vessels because, they are operated in high temperature. There are single specimen method, which used as evaluation of safety and integrity for reactor pressure vessels. In this study, elastic-plastic fracture toughness($J_{lc}$) and J-$Δ$a of SA 516/70 steel used as reactor pressure vessel steel are measured and evaluated at room temperature, 150$^{°}C $, 250$^{°}C $ and 370$^{°}C $ according to unloading compliance method.